Experimental Investigation and Parametric Optimization of Adhesively Joining Composite - Rahel, Haile (ASTU, 2022)
Composites Materials Are Used In Aerospace And Automotive Industries Replacing Aluminum And Titanium Alloys. As Demands Of Composites Increased In Complex Applications Leads To High Research Works For Joining The Parts By Adhesive Joining Techniques. Adhesively Bonded Joints Can Solve Problems Such As Joint Area Cracks, Corrosion And Wear During Welding Or Screwing Methods. Composite Joining By This Method Was Advantages Due To Uniform Stress Distribution Along The Bonded Areas WhichImproves Stiffness Than A Riveted Join. In This Research Study, A Small Scale LaboratoryComposite Adherends For Adhesively Purpose Was Prepared By Simple Hand Layup Method Using Polyester As Matrix And Nano Alumina Powder Of Particle Size ??? 50nm And Banana Fiber As Reinforcing Materials. Then Adhesively Joined Composite Samples Were Prepared By Binding The Adherends Using Abro Epoxy Adhesive. The Performance Of Bonding Schemes Was Related To Multiple Factors Like, Overlap Length, Joint Configuration And Environmental Factors. Nine Samples Were Made By Varying The Configuration Joint (Single Lap, Stepped And Scarf), Overlap Length Of 25 Mm, 30 Mm And 40mm And Temperature (0???, 20??? And 60???). Experimental Tests Were Conducted To Evaluate Mechanical Properties Of Tensile, Flexural, Compression And Fractography Analysis. Taguchi Based Grey Relational Analysis Was Used To Develop A Statistical Model To Describe The Relationship Between Mechanical Properties Of The Joint; Independent Parameters Were Selected To Optimize The Process Parameters. The Maximum Tensile, Flexural And Compression Strength Were 12.80mpa, 54mpa And 22.8mpa Respectively At Sample 9, Sample 7, And Sample 4 Respectively. The Minimum Tensile, Flexural And Compression Strength Was 5.12mpa, 18mpa, And 6.24mpa.The Failure Occure During The Mechanical Tests Were Adhesive, Cohesive, And Adherend Failure. Fractography Analysis Depicted That Even Though There Was Small Void At The Bonding Line, The Joint Of Composites Showed Better Bonding Between The Adherends And Adhesive. The Optimum Combination Obtained Through Taguchi Based Grey Relational Analysis Was Single Lap Joint, 30 Mm Overlap Length, And 20???. The Investigation Revealed The Suitability Of Overlap Length, Configuration Joint As An Effective Parameter In Adhesively Joined Composite.
Keywords: Composite, Matrix, Reinforcement Joint, Adhesive, Aderend, Temprature, Bonding, Taguchi, Grey relation analysis.